Growth and physiological responses of snapper (Pagrus auratus) and cobia (Rachycentron canadum) fed various inclusion levels of selenium supplemented lupin meal as fishmeal replacement diets - Pham, Duc Hung (Curtin University, 2016)
The nutritional effects of dietary selenium and lupin meal in snapper Pagrus auratus and cobia Rachycentron canadum were evaluated. Dietary selenium supplementation improved growth and physiological responses of cobia, but not in snapper. Dietary selenium supplementation improved growth, feed utilisation and physiological responses of cobia fed lupin-based diets. Both species showed symptoms of selenium toxicity after fed excessive selenium levels. Adverse effects were observed in snapper and cobia fed high inclusion levels of lupin.